2003
DOI: 10.1088/0965-0393/11/5/303
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of stress-induced phase transformations and grain nucleation at crack tips in Fe

Abstract: The molecular dynamics simulation technique is used to study a stressinduced new grain formation mechanism at the crack tip of a nanocrystalline α-iron sample at temperatures ranging from 100 to 600 K. The stress-induced formation of new bcc grains, created inside existing grains, is found to occur through a metastable bcc to fcc phase transformation at the crack tip of the sample. A Nishiyama-Wassermann orientation relationship is found between the original bcc grain and the fcc phase and a Kurdjumov-Sachs or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 40 publications
6
31
1
Order By: Relevance
“…This forced phase transformation results in a metastable displacive shear transition of bcc iron to closely packed fcc and hcp phases [46,47]. The orientation relationships between the transformed and untransformed regions were found to be similar to those observed for temperature-driven martensitic transformations in Fe and steels, and exactly the same as observed in the present study.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This forced phase transformation results in a metastable displacive shear transition of bcc iron to closely packed fcc and hcp phases [46,47]. The orientation relationships between the transformed and untransformed regions were found to be similar to those observed for temperature-driven martensitic transformations in Fe and steels, and exactly the same as observed in the present study.…”
supporting
confidence: 86%
“…4 One can see that orientation relationship between the grains in Fig. 3b completely identical to the OR between the grains bcc 1 and bcc 2 in the MD simulations of reference [46], and thus we provide the first direct experimental evidence for the existence of the processes shown in the simulation study.…”
Section: Stability Of Austenite Nanograinssupporting
confidence: 67%
“…Molecular dynamic simulation confirmed that the formation of nanocrystalline structure and dissolved carbides increased Gibbs free energy, providing driving force from bcc to fcc. Laptaoie [28] stated that the transformation from bcc to fcc was controlled by the stress. The fcc structure is not stable because it has a high energy make the transformation from bcc to fcc is reversible.…”
Section: Phase Transformation and Amorphization In The Weamentioning
confidence: 99%
“…They also discussed whether the grain size and impurities would improve the ductility of nanocrystalline metals. Furthermore, in the literatures [14,15] both intragranular and intergranular fracture were observed. Other people found that a material should not be simply classified as intrinsically brittle or ductile [16] because under some specific conditions of mechanical load, the nanocrystalline materials may be shown to exhibit either brittle or ductile fracture behaviour.…”
Section: Introductionmentioning
confidence: 99%